The use of Karate as a resource in the rehabilitatory process of a patient with sequels of cerebral vascular accident (CVA): an experience report in Occupational Therapy - Silva, Ewerling Cristina Reis da (2022)
This article aims to report the experience of Occupational Therapy students in the intervention of the case of a male patient, suffering from hemiplegia and hemiparesis resulting from two strokes. The interventions took place during the practice of a curricular component of the 5th semester of the Occupational Therapy course at the Universidade do Estado do Pará (UEPA). The patient was selected from the waiting list of patients with demands for neurological sequelae, trauma-orthopedics and rheumatic diseases, of the Physiotherapy and Occupational Therapy Unit (UEAFTO). The sessions were held twice a week, lasting 50 minutes, from August to November 2021. We chose to intervene with combined models such as the principles of Brain Plasticity, Restriction Therapy and Movement Induction and the technique of mirror therapy. In the interventions, Karate was used as a resource, as well as adaptations for Activities of Daily Living (ADL), and auxiliary adaptations for carrying out activities in the occupational therapy sections. The patient showed enthusiasm and greater engagement with the inclusion of karate in occupational therapy sessions, in addition, it was empirically observed that the patient presented a gain in Range of Motion in the Upper and Lower Limbs (MMSS/LL), ataxia was alleviated presenting greater stability in the MSE and gain of muscular strength. The combination of approaches and techniques added to the rescue of previous occupations contributed to positive results, in addition to improving the students' clinical reasoning and academic experience.